2004
DOI: 10.1002/pros.20024
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer and polymorphism D85Y in gene for dihydrotestosterone degrading enzyme UGT2B15: Frequency of DD homozygotes increases with Gleason Score

Abstract: Polymorphism D85Y in gene UGT2B15 correlates with differentiation of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…However, in the literature, both significant and null associations have been observed. The results from this study showed a significant increase in the risk for prostate cancer in individuals homozygous for the G allele, consistent with previous reports (Table 4) (MacLeod et al, 2000;Hajdinjak and Zagradisnik, 2004;Park et al, 2004). However, null associations of the UGT2B15 D85Y polymorphism have also been described.…”
Section: Ugt2b Variants: Aag Levels and Prostate Cancer Risksupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the literature, both significant and null associations have been observed. The results from this study showed a significant increase in the risk for prostate cancer in individuals homozygous for the G allele, consistent with previous reports (Table 4) (MacLeod et al, 2000;Hajdinjak and Zagradisnik, 2004;Park et al, 2004). However, null associations of the UGT2B15 D85Y polymorphism have also been described.…”
Section: Ugt2b Variants: Aag Levels and Prostate Cancer Risksupporting
confidence: 93%
“…However, the expression of all three genes has been measured in prostate cancer cell lines (Valentini et al, 2007). The association of the UGT2B15 D85Y polymorphism with prostate cancer has been examined with conflicting results (MacLeod et al, 2000;Gsur et al, 2002;Hajdinjak and Zagradisnik, 2004;Park et al, 2004;Cunningham et al, 2007). Similarly, numerous studies have explored the association of the UGT2B17 CNV and prostate cancer also with inconsistent conclusions (Park et al, 2006(Park et al, , 2007Gallagher et al, 2007;Karypidis et al, 2007;Olsson et al, 2008;Setlur et al, 2010).…”
mentioning
confidence: 99%
“…The authors concluded that the individuals who are homozygous for the low activity allele may be at increased risk of developing prostate cancer (odds ratio = 3.0; 95% confidence intervals 1.3-6.5). Three additional studies (Table 2) with larger number of individuals were recently published which further support this first observation [58][59][60]. The second androgen-conjugating enzymes expressed in the prostate, UGT2B17, have also attracted attention.…”
Section: Polymorphism In Ugt2b15 Gene and Deletion Of Ugt2b17 Genementioning
confidence: 68%
“…A lower enzyme activity could increase the amount of available dihydrotestosterone in the prostate, thereby increasing exposure to androgens and perhaps also the risk of PCa. Indeed, several studies have investigated the distribution of UGT2B15 alleles in prostate cancer patients and controls, concluding that patients who are homozygous for the low-activity allele may be at increased risk for developing prostate cancer [19][20][21][22]. Interestingly, there was also an increase in prostate cancer risk among individuals with UGT2B17 deletion polymorphism [23][24][25].…”
Section: Discussionmentioning
confidence: 95%